Profile of Nutrition and Hazards of Om-Elkholool (Donax Trunculus) and Gandofly (Ruditapes Decussatus) Clams from Alexandria, Egypt - Abd-Allah, Sherief Mohammed Sayed (International Journal For Research In Agricultural And Food Science, 2020)
Clams are delicate nutritious food; however they can harbor potential health hazards. The current work aimed to investigate and compare some of the nutritive criteria and hazards of Om-Elkholool (Donax trunculus) and Gandofly (Ruditapes decussatus) clams sold at Alexandria, Egypt. A total of 46 samples (22 of Om-Elkholool and 24 of Gandofly) were randomly collected from fish retailers during summer of 2017. Samples were analyzed for proximate composition (dry matter, moisture, protein, fat, and ash %). The carbohydrates and energy content was calculated. The count of coliforms, fecal coliforms, E. coli and Cl. perfringenes (MPN/g) was determined. Concentration (mg/kg) of lead and cadmium in 10 randomly selected samples of each type were estimated. The dry matter, moisture, protein, fat, ash and carbohydrates percentages mean values for Om-Elkholool “Om” samples were 30.37±0.22, 69.60±0.21, 8.49±0.14, 1.29±0.03, 18.63±0.09, and 1.99±11, respectively, while for Gandofly “Gd” samples were 16.81±0.21, 83.28±0.2, 8.69±0.13, 1.22±0.03, 3.43±0.09, and 3.37±10, respectively. The gross energy content (Kcal/100g) mean value was 53.55±0.88 for Om and 59.24±0.85 for Gd. Coliforms, fecal coliforms and E. coli (MPN/g) could not be counted in any of the samples of Om, while were counted in 75.0, 4.17, and 4.17% of Gd samples, respectively. Cl. perfringenes (MPN/g) was counted in 22.73 and 12.5% of Om and Gd samples, respectivly. Lead concentrations mean value (mg/kg) was 5.38±0.86 and 9.2±0.78, while cadmium mean value was 0.88±0.08 and 0.57±0.04, in Om and Gd samples, respectively. Lead concentrations exceeded the permissible limit in all the analyzed samples (100%) of Om and Gd, while cadmium concentrations exceeded the limit in 40 and 0.0% of the samples, respectively. The mean values of some studied items (dry matter, moisture, ash, carbohydrates, energy, lead, and cadmium) were significantly differ (P<0.05), while of some others (protein and fat) showed no significant difference (P>0.05). In conclusion, Om and Gd from Alexandria are nutritious with appreciable protein and ash content. They seem nearly parallel in nutritive value. However, they could pose a serious risk for human health (harbor potential bacterial pathogens, and toxic heavy metals) especially with respect to Gd. It is advised to properly cook rather than the habit of consuming them raw; and to be consumed in not large quantities and on sporadic rather than on regular bases.